Pola Pengobatan Stroke Iskemik Pada Pasien Lansia di Rumah Sakit Hasan Sadikin Bandung - Glenn Mark Togu; Lisda Amalia; Trully Deti Rose Sitorus (Majalah Kedokteran Indonesia, 2021)
Background: Ischemic stroke in Indonesia is one of the main causes of disability and mortality in elderly. Aging is related with the increase of comorbidities. The comorbidities in elderly increase the potential for polypharmacy prescribing which increases the incidence of drug side effects. This study’s purpose is to know the demographic characteristic, treatment pattern, and side effect of the treatment in elderly patients with ischemic stroke. Methods: This study is a descriptive study with a cross-sectional design which was conducted throughout September–October 2020. This study used secondary data from ischemic stroke patients’ medical records admitted in Dr. Hasan Sadikin Central General Hospital’s in 2015–2019, with simple random sampling.Result: Result of this study shows that most elderly patients with ischemic stroke were young elderly aged 60-69 years, male, with hypertension as the major risk factor. Polytherapy (2-4 drugs) was found in 79 patients and polypharmacy (greater than 5 drugs) was found in 21 patients. Six patients with polytherapy and four patients with polypharmacy experienced drug side effects. Drug side effects of treatment observed were stress ulcer, upper gastrointestinal bleeding, and anemia.Conclusions: The treatment patterns were dominated by polytherapy (2-4 drugs). The percentage of elderly patients with polypharmacy (greater than 5 drugs) experiencing side effects was more than those with polytherapy. Drug side effects were dominated by stress ulcer.